Dari Reaktif ke Disiplin Positif: Pelatihan Pengasuhan Orang Tua Remaja - Yohanes Budiarto (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service Program (PKM) aims to provide positive parenting training for parents of students at Tarakanita 3 Junior High School in Jakarta, involving 56 participants. This activity combines psychoeducation, inner child reflection, and emotional regulation exercises to help change parents' disciplinary patterns from a reactive-punitive approach to positive discipline based on the principle of “connection before correction.” The PKM was conducted in two sessions that emphasized self-awareness, mapping childhood parenting experiences, grounding and breathing techniques, and role-playing parenting responses in everyday situations. Qualitative data was collected through observation, focused discussions, and written evaluation sheets. The results showed an increase in parents' awareness of the connection between childhood trauma, emotions during parenting, and ways of correcting children. Participants also reported their intention to exercise more restraint before correcting, use positive language, and restore relationships after conflict. This parenting model was assessed positively for building healthier parenting of adolescents.